Radiological assessment of persistent retroperitoneal and lateral pelvic lymph nodes after neoadjuvant therapy for rectal cancer: An analysis of the United States Rectal Cancer Consortium. Issue 5 (16th July 2021) - Turgeon, Michael K.; Gamboa, Adriana C.; Keilson, Jessica M.; Maniko, Jeffrey; Maguire, Lillias; Hrebinko, Katherine; Holder‐Murray, Jennifer; Wiseman, Jason T.; Abdel‐Misih, Sherif; Hamdan, Saif; Hawkins, Alexander T.; Bauer, Philip; et al.
Abstract : Introduction: Management of retroperitoneal and lateral pelvic lymph nodes (RLPN) in rectal cancer remains unclear. With total neoadjuvant therapy (TNT), more patients have radiologic complete clinical response (rCR). We sought to evaluate the impact of radiographic persistent RLPN after neoadjuvant therapy on survival. Materials and Methods: Patients with rectal adenocarcinoma with isolated RLPN metastasis, who received neoadjuvant therapy before surgery were included from the United States Rectal Cancer Consortium database. Primary outcomes were recurrence‐free survival (RFS) and overall survival (OS). Results: Of 77 patients, all received neoadjuvant therapy, with 35 (46%) receiving TNT. Posttreatment, 33 (43%) had rCR while 44 (57%) had radiographic persistent RLPN. Median number of radiographic positive RLPN was 1 (IQR 1–2). Receipt of TNT was associated with radiographic RLPN rCR (OR 4.77, 95% CI 1.81–12.60, p < .01). However, there was no difference in RFS and OS between patients who achieved rCR or with persistent RLPN (all p > .05). Conclusions: Radiographic persistence of RLPN was not associated with worse survival in well‐selected patients and may not be a reliable indicator of pathological response. TNT may be the preferred management strategy to select patients given its association with rCR. Radiographic persistence of RLPN after preoperative therapy should not necessarily preclude surgery.